Предмет: Алгебра,
автор: Tatyana157
решите уравнение: (2x+5) (3x-7)+(2x-1) (2x+1)=(5x+3) (2x-5)
Ответы
Автор ответа:
0
раскрываем скобки,получается
6x^2-14x+15x-35+4x^2+2x-2x=10x^2-25x+6x-15
в левой части 2х и -2х сокращаются
приводим подобные
10x^2+x-35=10x^2-19x-15
10x^2 и -10x^2 сокращаются,получается
x-35=-19x-15
x+19x=-15+35
20x=20
x=20/20
x=1
Похожие вопросы
Предмет: Алгебра,
автор: IziCoffe
Предмет: Қазақ тiлi,
автор: Sonyjhh
Предмет: Биология,
автор: bazarbek200747
Предмет: Химия,
автор: lizka199719
Предмет: Физика,
автор: Penochka22